2011
DOI: 10.1007/s11665-010-9805-z
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Magnetic Properties of MnFe2O4 Octahedral Microcrystals

Abstract: MnFe 2 O 4 octahedra have been prepared by reaction of Mn 2+ ions and Fe 3+ in alkaline condition via heat treatment of the coprecipitation product. The as-prepared powders were characterized in detail by conventional techniques such as powder x-ray diffraction; field emission electron microscopy and transmission electron microscopy. Vibrating sample magnetometer was used to determine the magnetic properties at room temperature. The results show that the MnFe 2 O 4 octahedra were single crystals with cubic jac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 17 publications
1
6
0
Order By: Relevance
“…This inconsistent shape also found in some crystals prepared over base substrates [32]. The crystal shape of MnFe 2 O 4 has been studied previously as a function of calcination temperature, at temperatures ranging from 900–1200 °C [33]. The present nanooctahedral shape obtained was in line with that prepared after calcination at 1100 °C.…”
Section: Resultssupporting
confidence: 83%
“…This inconsistent shape also found in some crystals prepared over base substrates [32]. The crystal shape of MnFe 2 O 4 has been studied previously as a function of calcination temperature, at temperatures ranging from 900–1200 °C [33]. The present nanooctahedral shape obtained was in line with that prepared after calcination at 1100 °C.…”
Section: Resultssupporting
confidence: 83%
“…It can be seen from Figure 3B that the saturation magnetization of EG is close to zero. With additional magnetic octahedralMnFe 2 O 4 particles into EG, the value of saturation magnetization was found to be 16 emu/g, which is much lower than the theoretical magnetism value of bare MnFe 2 O 4 reported in the literature [23,24]. This is given that the MnFe 2 O 4 wrapped by non-magnetic graphite sheets presenting as antiferromagnetic layers on the surface may result in a decrease in magnetism of EG-MnFe 2 O 4 .…”
Section: Resultsmentioning
confidence: 60%
“…The emergence of new peaks with the addition of MnFe 2 O 4 into EG was also observed in the XRD spectrum. For instance, the appearance of peaks at 2θ = 30.10°, 35.50°, 43.10°, and 57.00°, respectively, stands for the (220), (311), (400), and (511) reflections of octahedral MnFe 2 O 4 [23,24], indicating the successful incorporation of magnetic particles to graphite layers. Additionally, the disappearance of peak at 44.32° and 54.54° in the XRD spectrum of modified EG indicated that graphite sheets were further expanded during the synthesis process with heating at 700 °C.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, manganese and iron ions are natural abundance and less toxicity, which are suitable for practical applications. [15,16] Kuo et al reported MnFe 2 O 4 /carbon black composite was synthesized by a co-precipitation method, which exhibits superior cycling stability as excellent electrode material in supercapacitor. [17] Besides, the micromorphology of electrode materials is an important factor that decides the electrochemical performance of a supercapacitor, which is beneficial to improve electrochemical performance.…”
Section: Introductionmentioning
confidence: 99%
“…Ternary manganese ferrite with a multi‐oxidation state promotes electrochemical reactions, enabling them high specific capacitance. Moreover, manganese and iron ions are natural abundance and less toxicity, which are suitable for practical applications [15,16] . Kuo et al.…”
Section: Introductionmentioning
confidence: 99%